2001
DOI: 10.1021/la0101853
|View full text |Cite
|
Sign up to set email alerts
|

Meso- and Microscopic Behavior of Spherical Polymer Particles Assembling at the Air−Water Interface

Abstract: Using the Langmuir Blodgett (LB) technique, monolayers of spherical polymer particles were investigated at the air-water interface. In this study, LB methods were used to examine particle interactions, packing, morphology, and viscosity of polymer films. Films composed of polymer microgels (diameters of 113-427 nm) having a block-copolymer dispersant were investigated through isotherm, atomic force microscopy imaging, and two-dimensional (2D) viscosity studies. During monolayer formation, the effect of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In the equation of state model of Fainerman et al [13,14], the decrease in apparent size of the adsorbed protein with increasing surface pressure is described as desorption of segments of the protein chain. However, from studies performed with non-unfolding particles (such as Stöber silica particles [15], glass microspheres [16], gelled polymer microbeads [17], latex particles [18], and colloidal silver particles [19]) surface pressure-surface area relations are found that are remarkably similar to those typical for proteins. Another observed phenomenon that has been related to protein unfolding after adsorption is the increase in surface pressure at longer time-scales, while little or no increase in adsorbed amount is measured [2,7,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the equation of state model of Fainerman et al [13,14], the decrease in apparent size of the adsorbed protein with increasing surface pressure is described as desorption of segments of the protein chain. However, from studies performed with non-unfolding particles (such as Stöber silica particles [15], glass microspheres [16], gelled polymer microbeads [17], latex particles [18], and colloidal silver particles [19]) surface pressure-surface area relations are found that are remarkably similar to those typical for proteins. Another observed phenomenon that has been related to protein unfolding after adsorption is the increase in surface pressure at longer time-scales, while little or no increase in adsorbed amount is measured [2,7,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted in [63] that the monolayer behaviour by compression and expansion is possibly affected by the contact angle hysteresis and dynamics of wetting. Further surface pressure/area isotherms of particle monolayers at fluid interfaces were studied also by other authors, such as [64][65][66][67][68][69][70][71].…”
Section: Surface Pressure/area Isothermsmentioning
confidence: 96%
“…3. Surface pressure Π as a function of monolayer coverage for polymeric particles 113 nm (Δ), data according to [71]; theoretical curve calculated from Eq. (3), (for details see [102]).…”
Section: Experimental Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Block copolymers have been used extensively as a surrounding and stabilizing matrix of the nanoparticles due to their possible bipolar nature and dedicated phase behavior. [10][11][12] The use of the Langmuir-Blodgett (LB) technique to produce monoparticular layers [13] has been demonstrated, too. Ring structures on the mm scale were found by several authors including those prepared with the LB technique.…”
Section: Introductionmentioning
confidence: 99%